Postharvest control of anthracnose in mangoes by fumigation with vinegar and ethanol vapours - Rachit Suwapanich; Warawut Krusong; Anthony Keith Thompson (My University, 2019)
Anthracnose disease of mangoes is caused by Collectotrichum gloeosporioides. A control method that does not include synthetic fungicides would be beneficial therefore fumigation, in an especially designed vapour exposure box, with vapour from upland rice vinegar and ethanol were tested in vitro on C. gloeosporioides isolated from mangoes and cultured on PDA. Fumigation times were 0, 5, 6, 7, 8, 9 or 10 min for ethanol and vinegar vapours separately and in mixtures at different ratios for 0, 10, 11, 12, 13, 14 or 15 min. Exposure to either ethanol vapour or vinegar vapour controlled both mycelial growth and conidia germination during subsequent storage for seven days at 28°C-32°C, but ethanol was more effective than vinegar and ethanol was more effective alone than in any of the combinations with vinegar. These results provide a successful organic anthracnose control method, but in vivo testing is recommended before commercial application.
Keywords: Vapours; Plant Pathogens and Fungal Diseases